Oxidative DNA damage in bone marrow cells of patients with low-risk myelodysplastic syndrome - Novotna, Bozena; Bagryantseva, Yana; Siskova, Magda; Neuwirtova, Radana (Leukemia research, 2009)
Bone marrow aspirates of 19 patients with low-risk myelodysplastic syndromes (MDS) and 14 control subjects were collected in order to assess the level of oxidative DNA damage. Glycophorin A positive and negative cells separated by miniMACS magnetic cell sorting were subjected to single cell gel electrophoresis (comet assay) combined with enzymes of base excision repair (endonuclease III and formamido-pyrimidine-glycosylase) that specifically recognize oxidized nucleotides. Compared to controls, MDS patients exhibited a significant increase of oxidative damage to DNA which could contribute to genomic instability and disease progression.
Keywords: refrakterní anemie; oxidační stres; poškození DNA; Male; Comet Assay; DNA Damage; Myelodysplastic Syndromes; buňky kostní dřeně; Anemia, Refractory; Aged; Case-Control Studies; mužské pohlaví; senioři; Anemia, Refractory, with Excess of Blasts; refrakterní anemie s nadbytkem blastů; myelodysplastické syndromy; senioři nad 80 let; lidé; ženské pohlaví; studie případů a kontrol; Humans; kometový test; Aged, 80 and over; Female; Oxidative Stress; Bone Marrow Cells; lidé středního věku; Middle Aged